POWER AND POLITICAL STABILITY DURING THE INFORMATION EPOCH’S TRANSFORMATIONS - Комарова, Т. Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
Today the world is experiencing an era of paradigm transformations. The information stage, which began in the mid-twentieth century, is changing industrial world. State of transition humanity has already passed in days of the beginning of a new era, in the Renaissance. Apparently, the acceleration of dynamics of social transformations in the 21st century will be even more obvious. What was previously required for thousand years, centuries, today is possible for several years. Societies that are lagging behind in certain parameters from the leaders of modern trends, have been able to quickly catch up on lost time. Instability, uncertainty as a state of modernity regarding different spheres of human existence, and in particular, politics are in many ways a logical consequence of the transition era. However, the more urgent is the development of question about stabilization factors, about responses to challenges both at global and regional, local, and even individual levels. The specificity of transformations of power as a type of social interaction, as communication, which is associated with the production and control of cultural codes, axiological meanings that are important for human life and communities, is investigated. At the information stage, communicative quality of power is particular importance for finding out possible principles of stability for a sociopolitical space. The challenges of present stage are ambivalent: between autocratic and democratic management techniques. In the context of the development of practices of the first type of Internet, the world that they create can become a place of total control of a new type. The complexity of challenges faced by global community, argues in favor of need for open and informal interaction, cooperation, social mutualism. Individualization and return to man as a microcosm, which harmonizes with the macrocosm (according to G.S. Skovoroda) reflects the real components of synergy as basis of social engineering, adequate to the challenges of modernity.